REFORMASI KEBUDAYAAN MASYARAKAT JEPANG - Sri Sudarsih (Diponegoro University, 2018)
The nation of Japan have experienced a slump since its defeat in World War II. The State of the community are truly of concern. The nation of Japan immediately first settled in many ways especially the cultural reform. The method used is a description and the interpretation. The success of the nation of Japan to build his country with cultural reforms. They change the mental attitude through the reform of customs that are no longer in accordance with the changing times. Consistency and continuity into the keyword success of the Nation of Japan. The process of reform for hundreds of years was able to change the character of the nation of Japan to reach its zenith.Key words: reformation; culture; character